Moving towards a successful medical-psycho-pedagogical centre: Analytical study of management aspects - Aziz Kasmi; Bouzekri Touri; Khaoula Khennou; Hind Baba (Образование и наука)
Introduction. Today, the concept of management has become increasingly complex. Many medical-social organisations now help to understand this complexity, enabling managers to support executives throughout their medical-social work.Aim. The aim of the present research is to explore the correlations between managerial aspects in medico-social organisations in order to understand their links and identify avenues for improvement to increase operational efficiency and quality of care.Methodology and research methods. The authors employed a quantitative approach, based on a correlational study rather than an experimental one. The sample consisted of 100 Medical-Psycho-Pedagogical Centres (CMPP) in the Ile-de-France region, France. To collect the information, the directors of these centres were invited to fill in the questionnaire sent by the Google Forms platform, via the e-mail addresses of each centre. The results were processed with IBM SPSS 29.Results and scientific novelty. The results showed that there were statistically significant correlations between the managerial criteria of a high and significant percentage. There was a very high level of significance between the aspects “Structure and team management” and “Patient data management” (98%), and between the aspects “Quality and safety of care” and “Structure and team management” (91%). As for “Inter-professional cooperation” and “Quality and safety of care” aspects, this was significant at 70%. Finally, the aspects “Accessibility and continuity of care”, and “Continuing education” correlate significantly at 85%.In sum, the findings demonstrate that, out of the 22 correlations that were computed, 20 relationships are significant (i.e. 90.90% of the relationships), attesting to the superior management structure of French centres.Practical significance. The contribution of the present study consists in identifying the dimensions of managerial aspects described in the review of management literature. Of course, the purpose of this work is not to justify one style or to privilege one style over another, but to contribute to the explanation of the reality of the management of health, social and medico-social establishments and to take them as a system to be followed in the management of CMPPs in Morocco.